Low pressure discharge initiated by microwave radiation with stochastically jumping phase - Karas’, V.I.; Artamoshkin, A.М.; Alisov, А.F.; Bolotov, О.V.; Golota, V.I.; Karas’, I.V.; Yegorov, А.М.; Zagrebelny, I.А.; Potapenko, I.F. (Вопросы атомной науки и техники, 2012)
Present results continue the line of the previous research. In this paper the conditions of a microwave discharge ignition, its stable maintenance in air by MWRSJP, and the pressure range at which required power is minimal are found. We experimentally examine also optical characteristics of the discharge plasma in a wide range of air pressure. In general the research aims to develop a new type of sources of optical radiation.